Features of teaching grammar in foreign language classes in non-linguistic institutions of higher education - K. Degtiarova; V. Zhyvolup; A. Karas; L. Kibenko; I. Lyakhova (Mukachevo State University, 2023)
Knowledge of the grammar of a foreign language at the proper level is a necessary component of language proficiency in general, and therefore teachers are faced with an urgent question of how to facilitate and accelerate the process of its assimilation. The purpose of the study is to theoretically substantiate the importance of mastering grammar for applicants of non - linguistic institutions of higher education and analyse the application of the proposed exercises. The methodology of the study consists in the application of theoretical (analysis of methodological literature on the problem of study, comparative analysis of grammatical phenomena of English and Ukrainian languages, analysis of educational publications on English for students of non-linguistic areas of training) and empirical research methods (observation of the level of grammatical competence of students; questionnaires and testing of students; an experiment that consisted in organising and conducting experimental training to test the effectiveness of the developed set of exercises that contribute to faster and more complete assimilation of the grammatical component of a foreign language). Techniques and means of teaching and activating grammatical structures in the study of a foreign language are examined. English language textbooks for non-linguistic institutions of higher education are analysed. The analysis of the use of exercises and internet resources aimed at mastering and fixing the necessary grammatical rules is conducted. The results of testing the teaching of English grammar on a communicative basis in a non-linguistic institution of higher education using professional-oriented educational texts as the basis for exercises are presented. The position that this approach contributes to maintaining students' motivation, activity, and independence is justified. Research training conducted based on the state biotechnological university confirmed the effectiveness of the proposed set of exercises in working with grammar based on professional texts. This technology can be used by teachers-philologists in teaching grammar of any foreign language, provided that they adapt accordingly, depending on the typical language difficulties and needs of students.